Evacuation of Delayed Packets in Networks - Sriee S.K.M, Vidhiya Madhu; S, Nandhini. (IJRDO -Journal of Computer Science Engineering, 2017)
The aim of this paper is to give idea of postponed packets in networks. At present the networks which we are using supports only two classes of traffic, it takes long time to service if there is any failure. Hence to solve all these problems a OCGRR technology has been developed. This is the advanced version of OCRR technology. It requires a processor of 500MHZ and above, ram of 128 mb and hard disk of 10 gb size. It makes use of jdk 1.5, windows 2000 server family operating system and sql server databases. In OCGRR, small rounds of a frame and a packet-by- packet are made used such that every stream inside a class can send only one packet in each small round. .In this packets of same class are sent to the destination. Before frame is scheduled, each output port data streams are stored in a separate Buffer .Buffers are placed in frames such that each frame consists of only one buffer. Once Scheduling is done transmission traffic occurs and data is transferred according to